The normal limit distribution of the normalized number of false solutions of a one system of nonlinear random equations over the field GF(2) - Slobodian, S.Ya. (Carpathian Mathematical Publications, 2014)
The theorem on a normal limit distribution of the normalized number of false solutions of a beforehand consistent system of nonlinear random equations over the field GF(2) is proved. The results with the additional condition on the number of nonzero components both false solutions and true solution of the solutions are obtained.